Natural herbal extract roles and mechanisms in treating cerebral ischemia: A systematic review - Yang, Jiashuo; Yu, Bo; Zheng, Jian (Frontiers in Pharmacology, 2024)
Background: Stroke has been the focus of medical research due to its serious consequences and sequelae. Among the tens of millions of new stroke patients every year, cerebral ischemia patients account for the vast majority. While cerebral ischemia drug research and development is still ongoing, most drugs are terminated at preclinical stages due to their unacceptable toxic side effects. In recent years, natural herbs have received considerable attention in the pharmaceutical research and development field due to their low toxicity levels. Numerous studies have shown that natural herbs exert actions that cannot be ignored when treating cerebral ischemia.Methods: We reviewed and summarized the therapeutic effects and mechanisms of different natural herbal extracts on cerebral ischemia to promote their application in this field. We used keywords such as "natural herbal extract", "herbal medicine", "Chinese herbal medicine" and "cerebral ischemia" to comprehensively search PubMed, ScienceDirect, ScienceNet, CNKI, and Wanfang databases, after which we conducted a detailed screening and review strategy.We included 120 high-quality studies up to January 10, 2024. Natural herbal extracts had significant roles in cerebral ischemia treatments via several molecular mechanisms, such as improving regional blood flow disorders, protecting the blood-brain barrier, and inhibiting neuronal apoptosis, oxidative stress and inflammatory responses.Conclusions: Natural herbal extracts are represented by low toxicity and high curative effects, and will become indispensable therapeutic options in the cerebral ischemia treatment field.